Controlling Coulomb correlations and fine structure of quasi-one-dimensional excitons by magnetic order - Liebich, M; Florian, M; Nilforoushan, N; Mooshammer, F; Koulouklidis, A D; Wittmann, L; Mosina, K; Sofer, Z; Dirnberger, F; Kira, M; Huber, R (Nature materials, 2025)
Many surprising properties of quantum materials result from Coulomb correlations defining electronic quasiparticles and their interaction chains. In van der Waals layered crystals, enhanced correlations have been tailored in reduced dimensions, enabling excitons with giant binding energies and emergent phases including ferroelectric, ferromagnetic and multiferroic orders. Yet, correlation design has primarily relied on structural engineering. Here we present quantitative experiment-theory proof that excitonic correlations can be switched through magnetic order. By probing internal Rydberg-like transitions of excitons in the magnetic semiconductor CrSBr, we reveal their binding energy and a dramatic anisotropy of their quasi-one-dimensional orbitals manifesting in strong fine-structure splitting. We switch the internal structure from strongly bound, monolayer-localized states to weakly bound, interlayer-delocalized states by pushing the system from antiferromagnetic to paramagnetic phases. Our analysis connects this transition to the exciton's spin-controlled effective quantum confinement, supported by the exciton's dynamics. In future applications, excitons or even condensates may be interfaced with spintronics; extrinsically switchable Coulomb correlations could shape phase transitions on demand.